Soil fertility mapping and development of nutrient management zones in maize-based cropping system of the savanna zone of Nigeria - Peter, H. (Bayero University, 2019)
There is a growing need for spatially continuous and quantitative soil information for improved farmers yields and environmental management. This study was aimed at mapping the spatial variability of soil properties with focus on delineating soil nutrient management zones (MZs) in a maize-based cropping system. Farmers’ fertilizer application rates were monitored in relation to the yield obtained. The study was conducted in Ikara, Soba, Doguwa, Bunkure, Faskari, Kankara, Malumfashi, Bakori, Kafur, Funtua, Rogo, Giwa, Birnin Gwari, Sabon Gari, Igabi, Makarfi, Tudun-wada, Lere and Kauru all found in the savanna agroecological zones of Nigeria. Two hundred and ninety three soils samples were analyzed and principal component analysis (PCA) was used to determine soil properties that accounted for more than 60% of variation in soil fertility of the study area. Semivariogram parameters were used to determine the nature of soil fertility spatial variability and prediction maps produced using krigging interpolation methods. Farmers were divided into 3 categories based on quantities of fertilizer each applied. Result from PCA was used to assign weights to soil properties for MZs map. Soil reation (pH), total nitrogen (TN), available phosphorus (Av.P) and organic carbon (OC) were assigned weight of 17.7 %, 11.5 %, 11.1 % and 11.1 % respectively. Total nitrogen, Av. P, Exch.K and ECEC had a nugget/sill ratio less than 25 % suggesting a strong spatial dependence. The prediction maps produced indicated that soil fertility of the study area increased towards the north. Soil fertility of the area was generally low with an average TN of 0.06 %, Av.P of 5.6 mg kg-1, OC of 0.66 % and ECEC of 5.6 cmol(+) kg-1. Sand dominated soils of the area (47 %) with an average silt content of 25 % and clay content of 27.8 %. Farmers who applied recommended fertilizer rates had an average yield of 2.5 t ha-1 and above recommended rates farmers had an average yield of 5.0 t ha-1. Below recommended rate farmers had an average yield of 1.5 t ha-1. For suitable maize production in the study area, organic and inorganic fertilizers are needed to supplement for TN, Av. P and OC deficiencies.